2016
DOI: 10.1063/1.4941234
|View full text |Cite
|
Sign up to set email alerts
|

SnTe microcrystals: Surface cleaning of a topological crystalline insulator

Abstract: Investigating nanometer and micron sized materials thought to exhibit topological surface properties that can present a challenge, as clean surfaces are a prerequisite for band structure measurements when using nano-ARPES or laser-ARPES in ultra-high vacuum. This issue is exacerbated when dealing with nanometer or micron sized materials, which have been prepared ex-situ and so have been exposed to atmosphere. We present the findings of an XPS study where various cleaning methods have been employed to reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Saghir et al [24] reported that a binding energy of 485.4 eV corresponds to Sn 2+ in SnTe, thus, for the present results it can be concluded that Sn 2+ are present in the films, which means that Sn substitutes Cd as both have the same oxidation state.…”
Section: Resultssupporting
confidence: 66%
“…Saghir et al [24] reported that a binding energy of 485.4 eV corresponds to Sn 2+ in SnTe, thus, for the present results it can be concluded that Sn 2+ are present in the films, which means that Sn substitutes Cd as both have the same oxidation state.…”
Section: Resultssupporting
confidence: 66%
“…The former corresponds to a 0 state, 74 and the latter is +4 as in TeO 2 . [57][58][59] In contrast to the EDX characterization which has a lower sensitivity, two prominent In peaks are observed in Figure 5d and the binding energies are 453.7 eV (3d 3/2 ) and 446.0 eV (3d 5/2 ) which correspond to a +3 oxidation state. 75 These results suggest that the sample surface is oxidized and forms XPS spectra taken at other spots on the first substrate show similar results ( Figure S5 and Table S1, Supplementary Information).…”
Section: -73mentioning
confidence: 93%
“…The Sn 3d spectrum in Figure 5b shows two peaks at ~ 496.0 eV (3d 3/2 ) and ~ 487.6 eV (3d 5/2 ), indicating a +4 oxidation state in contrast to the nominal +2 in SnTe. [57][58][59] The Te 3d spectrum in Figure 5c has two components with binding energies of 583.9 eV (3d 3/2 ), 573.5 eV (3d 5/2 ) and 587.8 eV (3d 3/2 ), 577.4 eV (3d 5/2 ), respectively. The former corresponds to a 0 state, 74 and the latter is +4 as in TeO 2 .…”
Section: -73mentioning
confidence: 99%
See 1 more Smart Citation
“…[11] The peaks of Sn 4þ and Te 4þ were associated with SnO 2 and TeO 2 on the TF surface. [47] The ratio of Sn 4þ species decreased and the ratio of Te 4þ species increased as the Te composition of the STX TFs increased.…”
Section: Rf Sputtering Power [W]mentioning
confidence: 94%